Increased mitochondrial oxidative stress in the Sod2 (+/−) mouse results in the age-related decline of mitochondrial function culminating in increased apoptosis - Kokoszka, Jason E. (The National Academy of Sciences, 2001)
To determine the importance of mitochondrial reactive oxygen species toxicity in aging and senescence, we analyzed changes in mitochondrial function with age in mice with partial or complete deficiencies in the mitochondrial antioxidant enzyme manganese superoxide dismutase (MnSOD). Liver mitochondria from homozygous mutant mice, with a complete deficiency in MnSOD, exhibited substantial respiration inhibition and marked sensitization of the mitochondrial permeability transition pore. Mitochondria from heterozygous mice, with a partial deficiency in MnSOD, showed evidence of increased proton leak, inhibition of respiration, and early and rapid accumulation of mitochondrial oxidative damage. Furthermore, chronic oxidative stress in the heterozygous mice resulted in an increased sensitization of the mitochondrial permeability transition pore and the premature induction of apoptosis, which presumably eliminates the cells with damaged mitochondria. Mice with normal MnSOD levels show the same age-related mitochondrial decline as the heterozygotes but occurring later in life. The premature decline in mitochondrial function in the heterozygote was associated with the compensatory up-regulation of oxidative phosphorylation enzyme activity. Thus mitochondrial reactive oxygen species production, oxidative stress, functional decline, and the initiation of apoptosis appear to be central components of the aging process.